-3(5y-7)+2(4y+6)=

Simple and best practice solution for -3(5y-7)+2(4y+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5y-7)+2(4y+6)= equation:


Simplifying
-3(5y + -7) + 2(4y + 6) = 0

Reorder the terms:
-3(-7 + 5y) + 2(4y + 6) = 0
(-7 * -3 + 5y * -3) + 2(4y + 6) = 0
(21 + -15y) + 2(4y + 6) = 0

Reorder the terms:
21 + -15y + 2(6 + 4y) = 0
21 + -15y + (6 * 2 + 4y * 2) = 0
21 + -15y + (12 + 8y) = 0

Reorder the terms:
21 + 12 + -15y + 8y = 0

Combine like terms: 21 + 12 = 33
33 + -15y + 8y = 0

Combine like terms: -15y + 8y = -7y
33 + -7y = 0

Solving
33 + -7y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-33' to each side of the equation.
33 + -33 + -7y = 0 + -33

Combine like terms: 33 + -33 = 0
0 + -7y = 0 + -33
-7y = 0 + -33

Combine like terms: 0 + -33 = -33
-7y = -33

Divide each side by '-7'.
y = 4.714285714

Simplifying
y = 4.714285714

See similar equations:

| 6(2x-4)=36 | | 5x-(3x-4)=17 | | 4x^2-28x+11=0 | | 6(13-2x)=50-x+46 | | 0+11y=7 | | 0+11y=y | | 2(4x+3)=12x+4-4x+2 | | 3(2x-1)+2(x+3)=3(x-2)-2(x-1) | | x^2-13x+24=0 | | 12x-7=1+10x | | -7=-y+4 | | x+(x-3007)=7803 | | X=0+4 | | 250=84-5(x-4) | | 5+8q=7+7q | | -5y-3=1-6y | | X^2+x+0.21=0 | | 4(x-2)=x-8+3x | | 12x+6-10x=2x+6 | | (n-2)*5=20 | | 22a+5-(a-7)=48 | | x(x-2)+(x-2)(x+2)=0 | | 2-.75k=.125k+9 | | 4(x+2)=5-(x+2) | | 10(9c-1)-14=88c+10 | | 3x+-3+5=5 | | 4(x+2)=5-(x-2) | | 0.6(x-2)=12.0 | | 8x+8-5x=3x+8 | | 7n=77 | | 12x-3=90+3(x-7) | | n-12=10 |

Equations solver categories